2023
DOI: 10.1002/anie.202301526
|View full text |Cite
|
Sign up to set email alerts
|

A Hemilabile NHC‐Gold Complex and its Application to the Redox Neutral 1,2‐Oxyarylation of Feedstock Alkenes

Abstract: We describe a AuI complex of a hemi‐labile (C^N) N‐heterocyclic carbene ligand that is able to mediate oxidative addition of aryl iodides. Detailed computational and experimental investigations have been undertaken to verify and rationalize the oxidative addition process. Application of this initiation mode has resulted in the first examples of “exogenous oxidant‐free” AuI/AuIII catalyzed 1,2‐oxyarylations of ethylene and propylene. These demanding yet powerful processes establish these commodity chemicals as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 60 publications
0
11
0
Order By: Relevance
“…Cl] = 0.02; 124.36 q, 3.8, (C13, II), Δδ 2-L2 = À0.15; 124.32 q, 3.8, (C13, I), Δδ 19,31, (I) , Δδ 3-[Au(iPr)Cl] = 0.02; 7.57, 2H, t, 7.8, HC 19,31,(II) , Δδ 3-[Au(iPr)Cl] = À0.05; 7.49, 2H, d, 8.0, HC 11,15,(II) , Δδ 3-L3 = À0.10; 7.46, 2H, d, 8.0, HC 11,15, (I) , Δδ 3-L3 = À0.13; 7.45, 1H, s, HC 8, (II) , Δδ 3-L3 = À1.10; 7.45, 4H, t, 7.8, HC 18,20;30,32, (I) , Δδ 3-[Au(ipr)Cl] = À0.01; 7.44, 4H, t, 7.8, HC 18,20;30,32,(II) , Δδ 3-[Au(ipr)Cl] = À0.02; 7.35, 1H, s, HC 8, (I) , Δδ 3-L3 = À1.20; 7.16, 2H, d, 8.0, HC 12,14, (I) , Δδ 3-L3 = 0.01; 7.09, 2H, d, 8.0, HC 12,14,(II) , Δδ 3-L3 = À0.06; 4.61, 2H, s, HC 9, (II) , Δδ 3-L3 = À0.11; 4.44, 2H, s, HC 9, (I) , Δδ 3-L3 = À0.28; 2.69, 4H, sep, 6.8, HC 22,25,34,37,(II) , Δδ 3-[Au(iPr)Cl] = 0.06; 2.67, 4H, sep, 6.8, HC 22,25,34,37, (I) , Δδ 3-[Au(iPr)Cl] = 0.04; 1.44, 24H, d, 6.8, HC 23,24,26,27,35,36,38,39,(IIa) , Δδ 3-[Au(iPr)Cl] = 0.08; 1.32, 24H, d, 6.8, HC 23,24,26,27,35,36,38,39,(Ia) , Δδ 3-[Au (iPr) Cl] = À0.04; 1.28, 24H, d, 6.8, HC 23,24,…”
Section: Multinuclear Nmr Spectroscopymentioning
confidence: 99%
See 3 more Smart Citations
“…Cl] = 0.02; 124.36 q, 3.8, (C13, II), Δδ 2-L2 = À0.15; 124.32 q, 3.8, (C13, I), Δδ 19,31, (I) , Δδ 3-[Au(iPr)Cl] = 0.02; 7.57, 2H, t, 7.8, HC 19,31,(II) , Δδ 3-[Au(iPr)Cl] = À0.05; 7.49, 2H, d, 8.0, HC 11,15,(II) , Δδ 3-L3 = À0.10; 7.46, 2H, d, 8.0, HC 11,15, (I) , Δδ 3-L3 = À0.13; 7.45, 1H, s, HC 8, (II) , Δδ 3-L3 = À1.10; 7.45, 4H, t, 7.8, HC 18,20;30,32, (I) , Δδ 3-[Au(ipr)Cl] = À0.01; 7.44, 4H, t, 7.8, HC 18,20;30,32,(II) , Δδ 3-[Au(ipr)Cl] = À0.02; 7.35, 1H, s, HC 8, (I) , Δδ 3-L3 = À1.20; 7.16, 2H, d, 8.0, HC 12,14, (I) , Δδ 3-L3 = 0.01; 7.09, 2H, d, 8.0, HC 12,14,(II) , Δδ 3-L3 = À0.06; 4.61, 2H, s, HC 9, (II) , Δδ 3-L3 = À0.11; 4.44, 2H, s, HC 9, (I) , Δδ 3-L3 = À0.28; 2.69, 4H, sep, 6.8, HC 22,25,34,37,(II) , Δδ 3-[Au(iPr)Cl] = 0.06; 2.67, 4H, sep, 6.8, HC 22,25,34,37, (I) , Δδ 3-[Au(iPr)Cl] = 0.04; 1.44, 24H, d, 6.8, HC 23,24,26,27,35,36,38,39,(IIa) , Δδ 3-[Au(iPr)Cl] = 0.08; 1.32, 24H, d, 6.8, HC 23,24,26,27,35,36,38,39,(Ia) , Δδ 3-[Au (iPr) Cl] = À0.04; 1.28, 24H, d, 6.8, HC 23,24,…”
Section: Multinuclear Nmr Spectroscopymentioning
confidence: 99%
“…13 C-NMR, d 7 -DMF, T = 25 C, relative to TMS, δ Cl] = 0.13; 8.19, 2H, s, HC 3,7, (II) , Δδ 4-[Au(iPr)Cl] = 0.11; 7.74, 2H, d, 8.0, HC 11,15, (I) , Δδ 4-L4 = À0.04; 7.72, 2H, d, 8.0, HC 11,15,(II) , Δδ 4-L4 = À0.16; 7.68, 2H, d, 8.0, HC 12,14,(II) , Δδ 4-L4 = 0.01; 7.67, 2H, d, 8.0, HC 12,14, (I) , Δδ 4-L4 = 0.00; 7.64, 2H, t, 7.8, HC 19,31, (I) , Δδ 4-[Au(iPr) Cl] = 0.02; 7.56, 2H, t, 7.8, HC 19,31,(II) , Δδ 4-[Au(iPr) Cl] = À0.06; 7.46, 4H, t, 7.8, HC 18,20;30,32, (I) , Δδ 4-[Au(iPr) Cl] = 0.00; 7.45, 4H, t, 7.8, HC 18,20;30,32,(II) , Δδ 4-[Au(iPr) Cl] = À0.01; 7.45, 1H, s, HC 8, (II) , Δδ 4-L4 = À1.12; 7.35, 1H, s, HC 8, (I) , Δδ 4-L4 = À1.22; 4.71, 2H, s, HC 9, (II) , Δδ 4-L4 = À0.10; 4.53, 2H, s, HC 9, (I) , Δδ 4-L4 = À0.28; 2.69, 4H, sep, 6.8, HC 22,25,34,37,(II) , Δδ 4-[Au(iPr)Cl] = 0.06; 2.68, 4H, sep, 6.8, HC 22,25,34,37, (I) , Δδ 4-[Au(iPr)Cl] = 0.05; 1.43, 24H, d, 6.8, HC 23,24,26,27,35,36,38,39,(IIa) , Δδ 4-[Au(iPr)Cl] = 0.07; 1.32, 24H, d, 6.8, HC 23,24,26,27,35,36,38,39,(Ia) , Δδ 4-[Au (iPr) Cl] = À0.04; 1.27, 24H, d, 6.8, HC 23,…”
Section: Multinuclear Nmr Spectroscopymentioning
confidence: 99%
See 2 more Smart Citations
“…Very recently, interest has been focused toward the development of catalysts bearing (C ∧ N) ligands. The same authors, and Zhang and Szostak, independently reported that the ImPy carbene-based ligand 11 represented a promising alternative to the use of MeDalPhos . The related (MIC ∧ N)­AuCl complex 10 developed by the group of Ribas appeared to be less reactive .…”
Section: Introductionmentioning
confidence: 99%